High-efficiency machining of single-crystal germanium using large-radius diamond tools. (16th January 2008) - Ohta, Tsutomu; Yan, Jiwang; Yajima, Shuuma; Takahashi, Youichi; Horikawa, Naoyuki; Kuriyagawa, Tsunemoto
Round-nosed diamond tools with various nose radii are used for cutting single crystalline germanium and fundamental machining characteristics are examined. It is found that when cutting with small radius tools, the principal cutting force is dominant and crater wear on rake face is significant. However, when cutting with large radius tools, the thrust force becomes significant and tool failure is caused by formation of an angular flank wear land. The use of a large radius tool at a high tool feed improves ductile machining efficiency by a factor of over ten, thus is useful for reducing infrared lens manufacturing costs.